Six new species of Rhyncaphytoptinae from northwestern China (Acari: Eriophyoidea: Diptilomiopidae) - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2006)
Six new species of diptilomipid eriophyoid mites from northwestern China are described and illustrated: Rhyncaphytoptus fargesis sp. nov. on Abies fargesii Frnach. (Pinaceae); Rhyncaphytoptus cotoneasteri sp. nov. on Cotoneaster sp. (Rosaceae); Rhyncaphytoptus abiesis sp. nov. and Rhyncaphytoptus fabris sp. nov. on Abies fabri (Mast.) Craib (Pinaceae); Rhinophytoptus cunninghamiae sp. nov. on Cunninghamia lanceolata (Lamb.) Hook. (Taxodiaceae) and Rhinophytoptus roxburghis sp. nov. on Rosa roxburghii Tratt. (Rosaceae). All species are vagrant on leaf surfaces. No damage to their host plants was observed.